ANALISIS PENERAPAN STANDAR AKUNTANSI DAN SISTIM PENGENDALIAN INTERNAL TERHADAP KUALITAS LAPORAN KEUANGAN - Alwi Alwi; M Rimawan; Aliah Pratiwi (INVOICE : JURNAL ILMU AKUNTANSI, 2020)
This study aims to analyze the effect of the adoption of Government Accounting Standards and Internal Control Systems on the Quality of Financial Statements of case studies conducted at the Regional Government Work Unit in Bima City Government. The research instrument used was a questionnaire with a Likert scale. The population and sample in this study is the Regional Work Unit as an accounting entity in the Bima City government area. The sampling method in this study uses a purposive sampling method with the Quota Sampling approach with each SKPD there are 3 respondents sampled namely the Head of Finance, Section Head as reviewer of the financial statements that have been prepared and Accounting Section Staff in charge of directly compiling financial statements. Data analysis techniques used in this study are the Validity Test, Reliability Test, Classical Assumption Test (Normality, Multicollinearity, Autokoerlasi) and Hypothesis Test with Multiple Linear Regression Test. The results of the analysis conducted in this study indicate that there is a positive influence on the application of Government Accounting Standards and Internal Control Systems to the Quality of Financial Statements in the Regional Government Work Unit of the City of Bima.